2012
DOI: 10.1002/jbm.a.34327
|View full text |Cite
|
Sign up to set email alerts
|

Study on in vitro release and cell response to alendronate sodium‐loaded ultrahigh molecular weight polyethylene loaded with alendronate sodium wear particles to treat the particles‐induced osteolysis

Abstract: The aim of this study is to investigate in vitro release and cell response to wear particles of ultrahigh molecular weight polyethylene loaded with alendronate sodium (UHMWPE-ALN), a potent bone resorption inhibitor. Wear particles of UHMWPE-ALN with different ALN contents (0.5 wt % or 1.0 wt %) and size ranges (<45 μm or 45-75 μm) were cocultured with macrophages (RAW264.7) and osteoblasts (MC3T3-E1), respectively. The in vitro ALN release was divided into three stages: an initial burst release, subsequent ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…First, commercially available Ti particles were used to generate osteolysis in the model rather than UHMWPE, which is the main cause of periprosthetic osteolysis [8,15]. However, it is well documented that both Ti and UHMWPE particles mimic the ability of authentic wear particles to activate osteoclast formation and function, to induce osteolysis in vivo [38].…”
Section: Discussionmentioning
confidence: 99%
“…First, commercially available Ti particles were used to generate osteolysis in the model rather than UHMWPE, which is the main cause of periprosthetic osteolysis [8,15]. However, it is well documented that both Ti and UHMWPE particles mimic the ability of authentic wear particles to activate osteoclast formation and function, to induce osteolysis in vivo [38].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of former mentioned studies that preoperative BMD measured at spine, hip, and forearm were major factors influencing periprosthetic bone loss and implant micromotion, we proposed that osteoporosis is the risk factor of aseptic loosening. Previous studies demonstrated that antiosteoporosis treatment significantly inhibits wear particle‐induced osteoclast formation in vitro . Epidemiology data also revealed that the use of antiosteoporosis drugs markedly reduces the overall risk of revision after THA .…”
mentioning
confidence: 99%
“…In a similar study, addition of lipopolysaccharide-coated polyethylene particles and addition of an antibody to sclerostin, an osteocyte-secreted molecule that interacts with LRP5/6 at the cell membrane, suppresses the Wnt signaling pathway [23]. Recent studies of osteolysis in the rabbit, a model that permits addition of particles into the medullary canal and analysis of cortical bone resorption, show that diverse treatment modalities inhibit bone turnover [30,34,61,62].…”
Section: Search Strategy and Criteriamentioning
confidence: 96%